(untitled) (Jurnal Pendidikan Fisika, 2020)
This study aims to: (1) describe the physics learning difficulties of students of class VIII in the Junior High School 1 Pomalaa.; and (2) describing any factors that cause learning difficulties Physics learners in class VIII Junior High School 1 Pomala. Subjects in this study were all learners VIIIA class and VIIID Junior High School 1 Pomalaa the second semester with the topic learning in motion and force. The research instrument consisted of multi-representation ability tests and interviews and then analyzed descriptively using a quantitative approach. Data analysis results obtained: The ability of multi-representation of students in the topic of motion and force is still relatively low with an achievement percentage of 71.86%. Learners are in a low category had a pattern of learning difficulties in understanding about the language, understand the basic concepts, analyze the image, determine the y-axis and the axis s, define symbols, set the equation and the difficulty in calculating. Learners medium category with a percentage of 27.35% achievement patterns of learning difficulties in understanding the basic concepts, force projection, determine the y-axis and s, erroneously define symbols, and erred in the calculation. Learners higher category has a pattern of learning difficulties in analyzing the image and determines the y-axis and the axis s on the graphical representation.